PIO Crisis Communication on Social Media Across Agencies: Social Listening, Public Perception, and Design Considerations - Wang, Di; Kogan, Marina (Proceedings of the International ISCRAM Conference, 2026)
Public information officers (PIOs) increasingly rely on social media for crisis communication, yet sustained social listening, especially for tracking public perception, is difficult to maintain under time, staffing, and platform constraints. We present an exploratory qualitative interview study of seven PIOs from government agencies in the U.S. Mountain West. Participants described different objectives on blue-sky days versus during emergencies: on blue-sky days, social media was used mainly for preparedness outreach and relationship-building, while during emergencies it was used to share incident updates, amplify partner agencies, and reassure affected communities. Participants also described social listening as important but unevenly sustained in practice. While many participants valued monitoring public questions, reactions to official messages or misinformation as important, most still relied on manual checks or engagement on their own accounts. Differences in PIO responsibilities, staffing, and agency role shaped whether social media work remained primarily one-way or included more sustained listening. Based on these findings, we derive design considerations for scheduling and pre-planning, monitoring, post review, and multi-agency coordination. Participants were generally more comfortable with bounded automation for monitoring, review, and other back-end support than with automation that produces public-facing messages, aside from limited and clearly constrained uses such as routine after-hours acknowledgments.